Health Resources and Strategies among Employed Women in Norway during Pregnancy and Early Motherhood - Marit Alstveit; Elisabeth Severinsson; Bjørg Karlsen (Hindawi Limited, 2015)
The number of women in paid employment is increasing. However, when becoming a mother for the first time, many seem unprepared for the challenge of balancing motherhood and work as well as for the impact on their health. The aim of this study was to investigate the health resources and strategies of employed women in Norway during pregnancy and early motherhood by means of salutogenic theory. A hypothetical-deductive interpretive approach based on Antonovsky's salutogenic theory was applied in a secondary analysis. A total of six themes were identified; three were classified as health resources when experiencing tension and three as health strategies. Salutogenic theory seems to be a useful framework for illuminating the health resources and strategies adopted by employed women who become mothers. The identified health resources when experiencing tension and the health strategies applied may have implications for maternity care professionals and employers in promoting the health of such women and supporting them to combine work and family life.